Work and occupational health during the pandemic in Brazil: critical notes on the chaos - Perpetua, Guilherme (Saúde e Sociedade, 2023)
As a major milestone in contemporary world history, the COVID-19 pandemic constituted both a sanitary crisis and one of the greatest humanitarian crises since last century. In Brazil, its outbreak enhanced the economic and political crisis already in course, creating an unprecedent scenario of social chaos which highlighted unemployment and labor precariousness issues. Based on the socio-spatial prism, this paper deconstructs narratives that, on the one hand, address the phenomenon as a biological fatality, naturalizing it, and, on the other, attribute to most (if not all) of the woes faced by Brazilian workers today.